Penggunaan Media Pemasaran Pada Mahasiswa Perguruan Tinggi Terbuka dan Jarak Jauh Di Indonesia - Wiradharma, Gunawan; Arisanty, Melisa; Budiman, Rahmat; Aditya Prasetyo, Mario (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2023)
Research aim: This study aimed to determine the preferences of marketing media used by UT students according to demographic characteristics. Design/Methode/Approach: This study uses a quantitative approach with survey methods through convenience sampling with non-probability techniques. This study distributed the questionnaire link and obtained respondents from as many as 6.155 UT students in Indonesia and abroad. The results of this study are the marketing media used by UT students based on demographic characteristics, namely age, gender, region of origin, and occupation using cross-tabulation analysis. Research Finding: The formulation of the research problem is how the demographic characteristics and cross-tabulation of the use of marketing media used by UT students. Theoretical contribution/Originality: In addition, the various choices of communication media encourage audiences to use communication media to meet their needs. Before determining this strategy, UT needs to know the marketing media used by students when they search for and obtain information about the open and distance higher education system. Practitionel/Policy implication: The implication of this research is the first step in making marketing and promotion strategies and knowing the effective and efficient use of marketing media. Research limitation: Students at Universitas Terbuka have different characteristics from those at other institutions, which can be seen in demography, geography, psychography, and behavior. To increase the Gross Enrollment Rate for Higher Education, UT has a target of one million students in 2024, so a planned, effective, and efficient marketing and promotion strategy is needed, as well as on target.